The agronomy and physiology of Brachiaria species - Fisher, Myles J.; Kerridge, Peter C. (International Center for Tropical Agriculture, 1996)
This paper reviews published and unpublished information on the physiological and agronomic characteristics associated with the widespread adaptation of Brachiaria species. Adaptation to shade, drought, flooding, rainfall, and defoliation are discussed. Strong regrowth under frequent defoliation is a major factor in persistence; however, this attribute probably results in the adoption of grazing management practices that work against the persistence of most legumes sown in association with Brachiaria. The negative aspects of pasture degradation and the positive effects of carbon sequestration should stimulate a search among new Brachiaria accessions for the physiological and agronomic characteristics that will make the genus even more useful.